Models, mysteries, and magic of molecules - Boeyens, Jan C. A. (Springer, 2017)
Molecular behaviour, which is no less than magical, holds the key to the understanding, not only of chemistry, but of all biology and of life itself. It is a mystery why molecular behaviour should remain poorly understood and why the authoritative theories of physics have produced no more than superficial models to elucidate this vital issue.